Drain current local variability from linear to saturation region in 28 nm bulk NMOSFETs. (February 2017) - Karatsori, T.A.; Theodorou, C.G.; Haendler, S.; Dimitriadis, C.A.; Ghibaudo, G.
Abstract: In this work, we investigate the impact of the source - drain series resistance mismatch on the drain current variability in 28 nm bulk MOSFETs. For the first time, a mismatch model including the local fluctuations of the threshold voltage ( Vt ), the drain current gain factor ( β ) and the source – drain series resistance ( RSD ) in both linear and saturation regions is presented. Furthermore, it is demonstrated that the influence of the source – drain series resistance mismatch is attenuated in the saturation region, due to the weaker sensitivity of the drain current variability on the series resistance variation. The experimental results were further verified by numerical simulations of the drain current characteristics with sensitivity analysis of the MOSFET parameters Vt, β and RSD .